Discovery and characterization of BRBV-sheep virus in nasal swabs from domestic sheep in China - Zhang, Yufei; Li, Yang; Qi, Lemuge; Hang, Tianyu; Wang, Peng; Wang, Yarong; Wu, Caili; Wang, Yongqin; Wang, Xufen; Hou, Lin; Ban, Yaxing; Zhang, Zhidan; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
The escalating occurrence of infectious disease outbreaks in humans and animals necessitates innovative, effective, and integrated research to better comprehend their transmission and dynamics. Viral infection in livestock has led to profound economic losses globally. Pneumonia is the prevalent cause of death in sheep. However, very few studies exist regarding virus-related pathogens in sheep. Metagenomics sequencing technologies in livestock research hold significant potential to elucidate these contingencies and enhance our understanding. Therefore, this study aims to characterize respiratory viromes in paired nasal swabs from Inner Mongolian feedlot sheep in China using metaviromic sequencing. Through deep sequencing, de novo assembly, and similarity searches using translated protein sequences, several previously uncharacterized and known viruses were identified in this study. Among these discoveries, a novel Bovine Rhinitis B Virus (BRBV) (BRBV-sheep) strain was serendipitously detected in the nasal swabs of domestic sheep (Ovis aries). To facilitate further molecular epidemiological studies, the entire genome of BRBV-sheep was also determined. Owing to the unique sequence characteristics and phylogenetic position of BRBV-sheep, genetically distinct lineages of BRBV in sheep may exist. A TaqMan-based qRT-PCR assay targeting the 3D polymerase gene was developed and used to screen 592 clinical sheep specimens. The results showed that 44.59% of the samples (264/592) were positive. These findings suggest that BRBV sheep are widespread among Inner Mongolian herds. This discovery marks the initial identification of BRBV in sheep within Inner Mongolia, China. These findings contribute to our understanding of the epidemiology and genetic evolution of BRBV. Recognizing the presence of BRBV in sheep informs strategies for disease management and surveillance and the potential development of targeted interventions to control its spread.